Use of a leukocyte-targeted peptide probe as a potential tracer for imaging the tuberculosis granuloma. (January 2018) - Locke, Landon W.; Kothandaraman, Shankaran; Tweedle, Michael; Chaney, Sarah; Wozniak, Daniel J.; Schlesinger, Larry S.
Abstract: Granulomas are the histopathologic hallmark of tuberculosis (TB), both in latency and active disease. Diagnostic and therapeutic strategies that specifically target granulomas have not been developed. Our objective is to develop a probe for imaging relevant immune cell populations infiltrating the granuloma. We report the binding specificity of Cyanine 3 (Cy3)-labeled cFLFLFK-PEG12 to human leukocytes and cellular constituents within a human in vitro granuloma model. We also report use of the probe in in vivo studies using a mouse model of lung granulomatous inflammation. We found that the probe preferentially binds human neutrophils and macrophages in human granuloma structures. Inhibition studies showed that peptide binding to human neutrophils is mediated by the receptor formyl peptide receptor 1 (FPR1). Imaging the distribution of intravenously administered cFLFLFK-PEG12 -Cy3 in the mouse model revealed probe accumulation within granulomatous inflammatory responses in the lung. Further characterization revealed that the probe preferentially associated with neutrophils and cells of the monocyte/macrophage lineage. As there is no current clinical diagnostic imaging tool that specifically targets granulomas, the use of this probe in the context of latent and active TB may provide a unique advantage over current clinical imaging probes. We anticipate that utilizing a FPR1-targeted radiopharmaceutical analog of cFLFLFK in preclinical imaging studies may greatly contribute to our understanding of granuloma influx patterns and the biological roles and consequences of FPR1-expressing cells in contributing to disease pathogenesis.